Twelve hour reproducibility of choroidal blood flow parameters in healthy subjects. Issue 4 (18th March 2004) - Polska, E; Polak, K; Luksch, A; Fuchsjager-Mayrl, G; Petternel, V; Findl, O; Schmetterer, L
Abstract : Aims/background: To investigate the reproducibility and potential diurnal variation of choroidal blood flow parameters in healthy subjects over a period of 12 hours. Methods: The choroidal blood flow parameters of 16 healthy non-smoking subjects were measured at five time points during the day (8:00, 11:00, 14:00, 17:00, and 20:00). Outcome parameters were pulsatile ocular blood flow as assessed by pneumotonometry, fundus pulsation amplitude as assessed by laser interferometry, blood velocities in the opthalmic and posterior ciliary arteries as assessed by colour Doppler imaging, and choroidal blood flow, volume, and velocity as assessed by fundus camera based laser Doppler flowmetry. The coefficient of variation and the maximum change from baseline in an individual were calculated for each outcome parameter. Results: None of the techniques used found a diurnal variation in choroidal blood flow. Coefficients of variation were within 2.9% and 13.6% for all outcome parameters. The maximum change from baseline in an individual was much higher, ranging from 11.2% to 58.8%. Conclusions: These data indicate that in healthy subjects the selected techniques provide adequate reproducibility to be used in clinical studies. Variability may, however, be considerably higher in older subjects or subjects with ocular disease. The higher individual differences in flow parameter readings limit the use of the techniques in clinical practice. To overcome problems with measurement validity, a clinical trial should include as many choroidal blood flow outcome parameters as possible to check for consistency.